2021
DOI: 10.3389/fonc.2021.642768
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Intratumoral Aryl Hydrocarbon Receptor in Primary Breast Cancer Depends on the Type of Endocrine Therapy: A Population-Based Cohort Study

Abstract: The aryl hydrocarbon receptor (AhR) is a master regulator of multiple pathways involved in breast cancer, and influences the estrogen receptor alpha (ER) and aromatase/CYP19A1. The purpose of this study was to elucidate the interplay between intratumoral levels of AhR and aromatase, patient characteristics (including AhR and CYP19A1 genotypes), clinicopathological features, and prognosis in breast cancer patients receiving adjuvant treatments. A prospective cohort of 1116 patients with primary breast cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(75 reference statements)
2
5
0
Order By: Relevance
“…10 Contrasting our proposition, Tryggvadottir et al, 2021, suggested that AhR was strongly associated with patients' ER-negative. 11 However, similar to Tryggvadottir et al, 2021 study findings, we reported that there was a statistically significant difference between AhR allelic variants and progesterone status. 11 However, this was not in agreement with findings of a study by Vacher et al, 2018.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…10 Contrasting our proposition, Tryggvadottir et al, 2021, suggested that AhR was strongly associated with patients' ER-negative. 11 However, similar to Tryggvadottir et al, 2021 study findings, we reported that there was a statistically significant difference between AhR allelic variants and progesterone status. 11 However, this was not in agreement with findings of a study by Vacher et al, 2018.…”
Section: Discussionsupporting
confidence: 89%
“…11 However, similar to Tryggvadottir et al, 2021 study findings, we reported that there was a statistically significant difference between AhR allelic variants and progesterone status. 11 However, this was not in agreement with findings of a study by Vacher et al, 2018. 12 Benoit et al, 2022 suggested that there was over-expression of AhR in HER2 negative cells but not over-expression in HER2 receptor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were some differences in the nuclear and extranuclear distribution of AhR protein in non-pathological breast ductal epithelial cells and invasive ductal carcinoma and AhR overexpression was associated with better prognosis of ER-negative and ER-positive invasive ductal carcinoma patients [ 58 ]. In another study on 436 breast cancer cases, it was concluded “that AhR expression is not a prognostic factor in breast cancer” [ 59 ]. There were correlations between AhR, and levels of several genes associated with inflammation and high levels of AhR repressor (AhRR) mRNA which predicted enhanced patient survival.…”
Section: Ahr In Breast Cancer: Prognostic Significancementioning
confidence: 99%
“…Another report indicated that the predictive value of the AhR was dependent on the lymph node status of the patient and concluded “that AhR is a marker of poor prognosis for patients with LN-negative luminal-like BCs” [ 61 ]. The results suggest that the prognostic value of AhR levels (mRNA and protein), intracellular location and AhR polymorphisms with respect to patient survival/disease recurrence is complex and dependent on many other factors, including prior patient treatment protocols [ 58 , 59 , 60 , 61 ].…”
Section: Ahr In Breast Cancer: Prognostic Significancementioning
confidence: 99%